"Underdiscussed, underused and underreported": pilot work in team-based qualitative research. (14th November 2016) - Morrison, Jane; Clement, Tim; Nestel, Debra; Brown, James
Abstract : Purpose: The authors, with disparate organisational affiliations and in different geographic locations, worked together on a qualitative multiple-case study of ad hoc supervisory encounters between general practice (GP) supervisors and GP-registrars. The purpose of this paper is to share our experiences and learning to highlight how valuable pilot work can be when conducting team-based qualitative research. Design/methodology/approach: This paper outlines the value of pilot work in consolidating whole team understanding of the research plan, using our experiences as an example. We first offer a synthesis of published literature relating to pilot work, especially in qualitative research approaches. Next, we outline and justify the pilot work undertaken for the ad hoc supervision study. Lastly, we use each researcher's voice to describe our experiences and then share the lessons we learned undertaking pilot work in qualitative research. Findings: We found that while pilot work can be useful in refining strategies, data collection processes and analytic instruments. There are further benefits in galvanising whole team understanding of the research plan, in encouraging reflexivity, in ensuring transparency of the research process, and for ethical considerations. Originality/value: There are few published papers or books which offer researchers guidance regarding pilot work, especially within a qualitative paradigm. Our experience shows there is value in planning and conducting pilot work. We believe others may benefit from our experience as they embark on team-based research.